Pengendalian Kepemilikan RSH Subsidi di Kelurahan Meteseh Kota Semarang - Siswanti, Dea Desita (Magister Pembangunan Wilayah dan Kota,Undip, 2013)
The Gerakan Nasional Pembangunan Sejuta Rumah (GN-PSR – a national program to provide a million housing) implemented by the government to provide housing for low income households has met several problems. One of the arising problems is that the subsidy for living-ready homes (Rumah Siap Huni – RSH) has often missed its target, such problem is observable in Puri Dinar Elok and Puri Dinar Asri in Meteseh Sub-district, Semarang City. This study attempted to formulate an ownership control mechanism for the subsidized housing in the study area so that it can meet its target more accurately using quantitative methods through interviews, questionnaires, institutional surveys and reviews of literature. Analysis on the subsidized housing in the study area showed that nearly 30% of the units were not owned by the target group, 9% of the units legally owned are not inhabited, and 6% were turned into investment commodities. This study suggested an anticipative control mechanism in the form of prerequisites that must be fulfilled by prospective buyers, and a residence control mechanism to ensure that the houses bought are in fact being used as a residence by the buyer.